Effect of changes in oscillatory amplitude on Paco2 and Pao2 during high frequency oscillatory ventilation. Issue 3 (1st May 2000) - Morgan, C; Dear, P R F; Newell, S J
Abstract : AIMS: To describe the relation between oscillatory amplitude changes and arterial blood gas (ABG) changes in preterm infants receiving high frequency oscillatory ventilation, using a multiparameter intra-arterial sensor (MPIAS). METHODS: Continuous MPIAS ABG data were collected after amplitude changes and stratified according to Fio 2 : high (> 0.4) or low (< 0.3). For each amplitude change, the maximum change (from baseline) in Paco 2 and Pao 2 over the following 30 minutes was determined. In total, 64 oscillatory amplitude changes were measured in 21 infants (median birth weight 1040 g; gestation 27 weeks). RESULTS: All amplitude increases produced Paco 2 falls (median −0.98 and −1.13 kPa for high and low Fio 2 groups respectively). All amplitude decreases produced Paco 2 rises (median +0.94 and +1.24 kPa for high and low Fio 2 groups respectively). About 95% of the change in Paco 2 was completed in 30 minutes. Amplitude changes did not affect Pao 2 when Fio 2 > 0.4. When Fio 2 < 0.3, amplitude increases produced a Pao 2 rise (median = +1.1 kPa; P < 0.001) and amplitude decreases a fall (median = −1.2 kPa; P < 0.001). CONCLUSIONS: After oscillatory amplitude changes, the speed but not the magnitude of the Paco 2 change is predictable, and a rapid Pao 2 change accompanies the Paco 2 change in infants with mild lung disease and a low Fio 2 .